Implementation of a Digital Correspondence Administration System to Improve Service Efficiency in Local Government Offices - Catur A Kisworo (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2026)
This study aims to implement and evaluate a Digital Correspondence Administration System to improve service efficiency in a local government office. The research adopts a System Development Life Cycle (SDLC) approach combined with a quantitative pre-test and post-test design to measure performance improvements. Key performance indicators include average processing time, document loss rate, service complaints, and user satisfaction. The results show a 61.11% reduction in processing time, a 92.86% decrease in document loss, and a 72.73% reduction in service complaints after system implementation. Additionally, the user satisfaction index reached 84%, indicating high acceptance among administrative staff. These findings demonstrate that workflow automation, digital archiving, and real-time tracking significantly enhance administrative efficiency, transparency, and service quality. The study confirms that digital transformation in correspondence management provides measurable and sustainable improvements in local government performance.